N6-methyladenosine methyltransferase plays a role in hypoxic preconditioning partially through the interaction with lncRNA H19. (17th November 2020) - Su, Yamin; Xu, Rongfeng; Zhang, Rui; Qu, Yangyang; Zuo, Wenjie; Ji, Zhenjun; Geng, Haihua; Pan, Min; Ma, Genshan
Abstract: N 6 -methyladenosine (m 6 A), a methylation in the N 6 position of adenosine especially in the mRNA, exerts diverse physiological and pathological functions. However, the precise role of m 6 A methylation in hypoxic preconditioning (HPC) is still unknown. Here, we observed that HPC treatment protected H9c2 cells against H2 O2 -induced injury, upregulated the m 6 A level in the total RNA and the expression of methyltransferase like 3 (METTL3), methyltransferase like 14 (METTL14), and long noncoding RNA (lncRNA) H19. Either knockdown of METTL3 or METTL14 notably reversed the HPC-induced enhancement of cell viability, anti-apoptosis ability, and H19 expression. Methylated RNA immunoprecipitation (IP) indicated that knockdown of METTL3 or METTL14 decreased m 6 A level in the lncRNA H19. Gain-of-function assay demonstrated that H19 overexpression could partially rescue the decreased protection mediated by METTL3 or METTL14 knockdown in HPC-treated H9c2 cells. RNA binding protein immunoprecipitation (RIP) assay showed that METTL3 and METTL14 could directly bind with H19. Our study identified a novel pattern of posttranscriptional regulation in HPC treatment. Since METTL3, METTL14, and lncRNA H19 were involved in HPC protection, they could be considered as potential biomarkers and therapeutic targets in HPC-derived cardiac rehabilitation and therapeutic approaches.